The Effectiveness of Environmental Policy in Addressing Climate Change - Sái Quỳnh Dao (Journal of Public Representative and Society Provision, 2023)
This research investigates the efficacy of environmental policies in addressing climate change as well as the effects those policies have on both the environment and civilization. The research was derived from a survey of the relevant literature as well as a case study of various policies implemented in a particular area. According to the findings of the research, certain types of policies, such as those based on markets, are more successful than others, such as policies based on volunteer participation, in terms of accomplishing environmental objectives. The research also shows that the amount of involvement and participation of stakeholders, as well as the social and political environment in which policies are enacted, all play a role in determining the degree to which policies are successful. In both the process of developing policies and making decisions, the significance of developing policies based on evidence, engaging relevant stakeholders, and maintaining a dedication to social equality and environmental justice is highlighted by the research. The findings of this study have implications for policy development and decision-making, and they highlight the need for an approach to environmental policy that is comprehensive and integrated, promotes sustainable development, and takes into consideration the complex and interrelated nature of environmental issues.